Maternal Feeding Styles and Food Parenting Practices as Predictors of Longitudinal Changes in Weight Status in Hispanic Preschoolers from Low-Income Families - Sheryl O. Hughes; Thomas G. Power; Teresia M. O’Connor; Jennifer Orlet Fisher; Tzu-An Chen (Journal of Obesity)
Objective. The aim was to investigate the influence of feeding styles and food parenting practices on low-income children’s weight status over time. Method. Participants were 129 Latina parents and their Head Start children participating in a longitudinal study. Children were assessed at baseline (4 to 5 years old) and again eighteen months later. At each time point, parents completed questionnaires and height and weight measures were taken on the child. Results. The indulgent feeding style (parent-report at baseline) was associated with increased child BMI z-score eighteen months later compared to other feeding styles. Authoritative, authoritarian, and uninvolved feeding styles were not significantly associated with increased child BMI z-score. Child BMI z-score at Time 1 (strongest) and maternal acculturation were positive predictors of child BMI z-score at Time 2. Maternal use of restriction positively predicted and maternal monitoring negatively predicted Time 2 BMI z-score, but only when accounting for feeding styles. Conclusion. This is the first study to investigate the impact of feeding styles on child weight status over time. Results suggest that indulgent feeding predicts later increases in children’s weight status. The interplay between feeding styles and food parenting practices in influencing child weight status needs to be further explored.